PENGARUH PEMBERIAN PENTAGAMAVUNON-0 PADA AKTIVITAS GLUTATION-S-TRANSFERASE PADA HATI TIKUS SECARA IN VIVO - Sudibyo Martono; Supardjan Amin M; Siti Zahliyatul Munawiroh (Jurnal Ilmiah Farmasi, 2004)
ABSTRACTGlutathione S-transferase is amount of enzymes catalyze conjugation reac-tion of glutathione(GSH) with electrofilic endogen compound or electrofilic xenobiotic. At the particular cancer there isincreasing GST, especially on mu and phi class that it cause therapy on cancer cell by citostaticdrug (commonly as electrofilic compound) not effectively. Pentagamavunon-0 (PGV-0) is antiinflammationcompound. Base on in vivo research denoted this compound has five timesstrengthened than curcumin to inhibit GST enzyme activity. But using PGV-0 by in vivo to GSTactivity never report or publish yet.This research was done by measuring isolated GST enzyme activity from rat liver was given invivo PGV-0, with nine groups treatment. Each group consist of control group without treatment,control group CMC-Na 0.5 % per oral and intraperitoneal DMSO, group with doses treatment ofPGV-0 20, 40, 80 and 160 mg/Kg BB per oral, rat group was given benzo(a)pirene (BP) 1 mg/KgBB i.p. and group was given BP 1 mg/Kg BB i. p. and PGV-0 80 mg/Kg BB per oral. GST enzymeactivity is measured from reaction of conjugate GSH and DCNB that it’s absorption/minute. Base onrate (absorption/minute) GST enzyme activity can be accounted. Then inhibition percentage can beaccounted from each rat treatment compared with control without treatment and solvent control.Analyze use statistic test (Kruskal-Wallis then continued by Mann-Whitney test), to know specificdifferent of GST class mu enzyme activity in rat liver at each treatments group.Result research denoted that PGV-0 give inhibition effect to GST class mu activity of rat liver byin vivo. Doses level did not give proportional result to GST class mu activity of rat liver. Doses levelof PGV-0 give optimum result to GST class mu activity of rat liver inhibition at 80 mg/Kg BB withinhibition value 19,99 % compared with CMC-Na as solvent.Key word: pentagamavunon-0, in vivo, glutathione S-transferase, inhibition